Faktor-faktor yang Mempengaruhi Permintaan Tempe di Kecamatan Sukomanunggal Kota Surabaya - Firdaus, Intan Arsyta; Pratomo, Gigih (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2024)
This study discusses the factors that influence the demand for tempeh in Sukamanunggal District, Surabaya City. The independent variables consist of the price of tempe, the price of white tofu, the level of income, the type of tempe, and the number of dependents while the dependent variable is the demand for tempe. This study uses quantitative methods, and the sample used is 398 respondents with the slovin calculation formula. The analytical method used is multiple linear regression. The results of the simultaneous test of this study showed that the price of tempeh, the price of white tofu, the level of income, the type of tempeh, and the number of dependents had a significant influence on the level of demand for tempeh in the community of Sukamanunggal District, Surabaya City. The partial test results show that the price of tempeh, the price of white tofu, and the level of income have a positive and significant influence on the level of demand for tempeh in the community of Sukamanunggal District, Surabaya City. While the type of tempe, and the number of dependents have a negative and significant effect on the level of demand for tempeh in the community of Sukamanunggal District, Surabaya City.